Correlated Imaging of the Equine Hyoid Apparatus Using CT, Micro-CT, and Histology - Hartl, Bettina; Egerbacher, Monika; Kneissl, Sibylle Maria (Frontiers in Veterinary Science, 2021)
Background: Detailed radiological evaluation of the normal hyoid apparatus by computed tomography (CT) has not yet been conducted. Thus, it is unclear what type of junction connects the different parts of the equine hyoid apparatus. Objectives: To describe the normal CT anatomy of the equine hyoid apparatus, and to determine the junction type that connects the different parts of the hyoid apparatus. Study Design: Combination of retrospective study and prospective cadaver study. Methods: The medical records of horses that underwent head CT scans from 2009 to 2018 were retrieved. Inclusion criteria for the CT scans were visibility of at least two of the four junctions of the hyoid apparatus. CT images were analyzed in three different planes. Additionally, 10 cadaver heads were processed using CT, micro-CT of selected joints, and histology of all joints. Results: CT scans of 200 horses fulfilled the inclusion criteria. The tympanohyoid cartilage consisted of hyaline cartilage. Areas of mineralization within the cartilage were visible on CT scans as early as 2 years of age. The epihyoid was not fused with the stylohyoid in one-third of the horses. All horses younger than 2.5 years showed three ossification centers of the basihyoid, and all horses younger than 1.5 years had a non-fullydeveloped lingual process. In total, 10 of 11 horses between 1.5 and 3 years had separate ossification centers of the lingual process. We found a synchondrosis between the styloid process and the stylohyoid bone. The basihyoid and thyrohyoid, as well as the stylohyoid and epiyhoid were connected by a synostosis in two-thirds of the horses. The remaining parts were connected to one another by synovial joints. Main limitations: The junctions studied by histologic examination were from older horses, therefore growing patterns of different bones could not be totally clarified. Conclusion: The temporohyoid joint is a synchondrosis. The epihyoid is an ossification center of the stylohyoid and fuses with the stylohyoid in two-thirds of horses. The lingual process has a separate ossification center.